Distribution of zooplankton biomass in the Barents Sea in autumn 1997. - Musaeva, Eteri I; Gagarin, Vladimir I (PANGAEA, 2000)
Samples of zooplankton were collected in the Barents Sea during cruise 11 of R/V Akademik Sergey Vavilov in September-October 1997. Three different sampling methods were used: 30 l bottle, Judey net, and BR net. More than 40 species of zooplankton were revealed. The greatest species diversity occurred in zones of junction of waters of different origin. Within the 100 m upper water layer zooplankton biomass was rather high: aver. 32 g/m**2. The highest biomass was observed in the northeastern part of the region under study and over the shelf of the Russkaya Gavan' Bay. The lowest biomass occurred in the southern part and in the region of the Gusinaya Banka. The average autumn value of zooplankton biomass in the 100 m upper layer (321 mg/m**3) slightly exceeded the multiannual average for the summer period (200 mg/m**3)
Occurrence of species-indicators and zooplankton biomass in the Barents Sea in September-October 1997
Keywords: Akademik Sergey Vavilov; Archive of Ocean Data; ARCOD; ASV11; ASV11-1067P; ASV11-835P; ASV11-847P; ASV11-860P; ASV11-875P; ASV11-891P; ASV11-966P; ASV11-985P; ASV11-991P; Barents Sea; MULT